Comparative, Topographically-Based Evaluation of Behavioural Phenotype and Specification of D1-Like:D2 Interactions in a Line of Incipient Congenic Mice with D2 Dopamine Receptor "Knockout" - Clifford, Jeremiah J. (2001)
Phenotypes were assessed topographically in mice lacking functional D2 dopamine receptors [‘knockouts’], using an ethologically based approach to assess all behaviours in the natural repertoire. D2-null mice evidenced an ethogram characterised initially by modest reductions in locomotion and shifts in rearing topographies. Subsequently, topographies of behaviour habituated similarly for wildtypes and ‘knockouts’. Following challenge with the D2-like agonist RU 24213, both inhibition of rearing at a lower dose and induction of stereotyped sniffing and ponderous locomotion at higher doses were essentially absent in D2-null mice. Following challenge with the D1-like agonist A 68930, vacuous chewing was released in D2-null mice. This topographical approach to phenotypic characterisation implicates: (i) the D2 receptor in these D2-like agonist effects and in oppositional D1-like: D2-like interactions; and (ii) the operation of material compensatory processes consequent to the developmental absence of D2 receptors which are able to maintain ethological function under tonic, ‘naturalistic’ conditions but not under ‘phasic’ challenge.